Conversational styles and gender: Analyzing informal conversation amongst students and lecturers at Universiti Putra Malaysia - Abd Rahim, Normaliza; Roslan, Siti Nur Aliaa; Roslan, Aiman Mustaqim; Sujud, Arba'ie; Zainon Hamzah, Zaitul Azma (Journal of the World Universities Forum, 2008)
Conversational styles provide a more meaningful feedback when the system needs to know not only the topic of the conversation, but also have an idea of the emotional content of the conversation and the conversational style of the interaction. Positive and negative attitudes can be detected based on the word choice of the speaker. This study is to find out how the differences in communication styles often lead to positive impact towards learning. This also includes the consequences of the communication including slower progression in language development. This study investigates whether the gender schemas have strong effects when men are minority at a university. This study consisted of 20 male and female students who were picked at random and a lecturer volunteered from Universiti Putra Malaysia (UPM). The students’ conversation with the lecturers were taped and analyzed accordingly. It is found that good conversational styles often lead to positive impact towards learning. 12 students had good conversational styles and therefore lead to faster progression in language development. These students are female. 8 students failed to understand the importance of good conversational styles and therefore had slower progression in language development. The students were not exposed to the positive style of conversation. The students were taught the right way of communicating with the lecturers. This was done by the researcher. It is hoped that the students at UPM able to learn the right way of communicating with the lecturers at UPM.